Reconstructing the Authority for Managing Seized Assets and State-Confiscated Property under Presidential Regulation No. 155 of 2024 - Yabes Marlobi Sirait; M.J. Saptenno; A.D. Bakarbessy (JURNAL MAHASISWA YUSTISI, 2026)
The management of seized assets and state-confiscated property constitutes an essential component of Indonesia’s criminal justice system, particularly in ensuring legal certainty, accountability, asset preservation, and the effective execution of court decisions. Presidential Regulation No. 155 of 2024 introduces an important institutional development by restructuring the authority and organizational framework related to the management of seized and confiscated assets. This study aims to analyze the reconstruction of such authority and examine its implications for institutional coordination and asset-management effectiveness. The research employs a normative juridical method using statutory and conceptual approaches, focusing on the relevant regulatory framework governing seizure, confiscation, storage, administration, and disposal of assets. The study finds that the reconstruction of authority requires a clear distribution of institutional responsibilities, integrated asset administration, strengthened supervision, and effective coordination among law-enforcement institutions. Presidential Regulation No. 155 of 2024 provides a significant foundation for improving governance, although its implementation requires regulatory harmonization and institutional consistency. The study concludes that an integrated and accountable management framework is necessary to prevent overlapping authority, preserve asset value, and strengthen legal certainty in managing seized assets and state-confiscated property.